Adaptive Policy Education in the VUCA Era for Jetis Sidoarjo Batik Craftsmen - Attalansyah, Amrizal; Anshori, M Isa (Journal of Business Management and Economic Development, 2024)
Industry 4.0 has brought a major transformation in the industrial paradigm, with digital technology that continues to develop and the start of the era of volatility, uncertainty, complexity and ambiguity (VUCA) making businesses have to think about strategic steps to maintain sustainability and resilience. Therefore, every business is required to be adaptive, especially in making policies and managing them. Kampung Batik Jetis Sidoarjo, which is a center for written batik that has existed since the 1900s, is also not immune from these challenges. The purpose of this study is to determine the description of the adaptive policies of Batik Jetis Sidoarjo craftsmen in facing the VUCA era. The method of writing scientific articles uses qualitative research methods and data collection techniques in the form of interviews and observations. This research activity explains the adaptive policy strategies of batik craftsmen and the efforts that can be made to face the VUCA era. The results showed that Jetis batik craftsmen rely on strong communication relationships with customers to help craftsmen confidently face the VUCA era.